Introduction to the practice of statistics - David S. Moore (W.H. Freeman and Company, 2009)
Berisi : Statistical applets, Tables, Data sets, Suplemental Material, Companion Chapters, Statistics in Practice, EESEE (access Code & Internet Required), CrunchIT (Access Code & Internet Required)